Socially inclusive adaptation to support equitable resilience in Baringo county, Kenya - Bullock, Renee; Majiwa, Hamilton; Ndiwa, Nicholas; DuttaGupta, Tanaya (International Livestock Research Institute, 2025)
The AICCRA Kenya Cluster implemented socially inclusive locally led adaptation (LLA) initiatives in Baringo County to strengthen climate adaptation and resilience. This report documents activities that bundled technical capacity building with gender responsive and transformative approaches in climate smart agriculture and climate information services. Community conversations guided the prioritization and planning of activities to build capacities in drought-tolerant crop and vegetable production and improved livestock practices. Over 2,300 participants, 52% of whom were women were reached and benefitted. Women led and learned in family led field days and peer exchange events. Gender forums and dialogues were spaces in which community members, including elders and leaders of customary institutions, discussed and proposed actions to expand women’s decision making. Climate information service channels included radio and WhatsApp. Base and endline surveys demonstrated significant uptake of CSA, CIS, and positive changes towards equitable norms and practices.